Oncologic Head and Neck Reconstructive Microsurgery during the COVID-19 Pandemic in Dharmais Cancer Hospital-National Cancer Center, Jakarta, Indonesia - Mukarramah, Dewi Aisiyah; Rini, Irena Sakura; Sofyan, Rian Fabian; Kiat, Muhammad Irsyad; Iskandar, Iskandar; Ritana, Azmi; Brahma, Bayu (Journal of Reconstructive Microsurgery Open, 2021)
Background Head and neck cancer is one of the leading cancers worldwide. Complex head and neck procedures are potentially aerosol-generating and considered high risk for coronavirus disease 2019 (COVID-19) transmission between the patients, surgeons, and other health-care workers (HCWs). Several adjustments in the microsurgery procedure were needed. The COVID-19 protocol was developed and applied to minimize the COVID-19 transmission. The study objectives were to describe the preoperative, intraoperative, and postoperative protocols applied and the characteristics of patients who underwent head and neck reconstructive microsurgery during the COVID-19 pandemic in Dharmais Cancer Hospital-National Cancer Center.Methods This study was a retrospective descriptive study of patients who underwent head and neck reconstructive microsurgery between March 2020 and December 2020 in the plastic surgery department and surgical oncology department, Dharmais Cancer Hospital-National Cancer Center, Jakarta, Indonesia. The patients' characteristics including sex, age, location of the defects, the flap type, flap survival, and complications were obtained from medical records and analyzed using SPSS version 23.Results There were 55 patients, 30 (54.54%) patients were female, and 25 (45.45%) patients were male. The mean age at the time of surgery was 51.32 ± 1.85 years. The most common cancer type was squamous cell carcinoma for 49.09% (n = 27/55). The most frequent location was tongue for 25.45% (n = 14/55). Anterolateral thigh flap was also the most used flap in this study for 50.91% (n = 14/55). The overall survival rate of this study was 83.64% (n = 46/55). There were nine patients (16.36%) who were found with postoperative complications. There was no nosocomial infection with COVID-19 for patients, surgeons, and other HCWs.Conclusion Microsurgery can be performed even in the COVID-19 pandemic as the gold standard for oncologic head and neck reconstruction by applying protocols to protect the patients, surgeons, and other HCWs.
Keywords: head and neck reconstruction; microsurgery; free flap; COVID-19 pandemic